Solid‐state Synthesis of Ni Decorated Needle Coke as Low‐cost Pt‐free Counter Electrode for Efficient Dye‐sensitized Solar Cells. Issue 26 (12th July 2021) - Wei, Liguo; Mao, Wei; Yu, Furong; Su, Ting; Chen, Jie; He, Huiyi; Zou, Mingyue; Wang, Shaoji; Lin, Jianmin
Abstract: To seek a Pt‐free carbon material counter electrode for dye‐sensitized solar cells (DSSCs), the electrocatalytic activity of needle coke (NC) for the reduction of triiodide in DSSCs was investigated, and further improved by decorating with Ni to prepare Ni decorated needle coke (Ni‐NC) via a one‐step solid‐state synthesis method. It is found that the NC is a potential carbon counter electrode material for DSSCs due to its high‐density anisotropy with considerable conductivity. Although the decoration of Ni may sacrifice certain conductivity of NC, the electrocatalytic activity of Ni‐NC towards reduction of triiodide was better than that of NC. To obtain a balanced point of conductivity and electrocatalytic performance for Ni‐NC, the loading amount of Ni together with the solid‐state synthesis conditions were also studied. It is indicated that these parameters also have some effect on the performance of Ni‐NC. Under the optimized conditions, the DSSCs based on Ni‐NC counter electrode achieve an 77 % higher energy conversion efficiency of 4.39 % than that of NC counter electrode (2.48 %), and comparable to the value (5.34 %) obtains with Pt counter electrode. It is an efficient way to improve the performance of NC by decorating with Ni via a facile solid‐state synthesis method, and promote the application of needle coke as carbon counter electrode materials in DSSCs. Abstract : It is an efficient way to improve the performance of needle coke by decorating with Ni via a facile solid‐state synthesis method, and promote the application of needle coke as carbon counter electrode materials in dye sensitized solar cells. Under the optimized conditions, the cells based on this counter electrode achieve an higher energy conversion efficiency than that of needle coke counter electrode, and comparable to the value obtains with Pt counter electrode.